2011
DOI: 10.1590/s1516-635x2011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric root and annato seed in second-cycle layer diets: performance and egg quality

Abstract: TZTaÚ6C\mmb_TagX66 FT_WTa[T8FC5@beTXf=8WX Ghe`Xe\VEbbgTaW4aaTgbFXXW\aFXVbaW6lV_X?TlXe 7\Xgf-CXeYbe`TaVXTaW8ZZDhT_\gl fh_Yhe T`\ab TV\W TaW _lf\aX _XiX_f TVVbeW\aZ gb g[X eXVb``XaWTg\bafbYEbfgTZabXgT_!%##(XkVXcgYbe c\Z`XagVbagXagGTU_X$!FbeZ[h`eXc_TVXW(#bY Vbea\aT__W\Xgf!4aaTgbfXXWfTaWghe`Xe\VebbgfjXeX jTf[XWWe\XWYbe%'[\aTYbeVXWiXag\_Tg\babiXaTg *(%6ZebhaWTaWf\XiXW!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 7 publications
6
15
0
3
Order By: Relevance
“…This is similar to previous studies (Rowghani et al, 2006;Laganá et al, 2011;Abiodun et al, 2014). In the present study, improvement in yolk colors was observed 7 days after feedingthe test diets, and yolk color hanged rapidly in a response to feeding green algae, showing the average values were higher than the control depending on the treatments, then it remained constant until observation of day 42.…”
Section: Egg Qualitysupporting
confidence: 93%
See 3 more Smart Citations
“…This is similar to previous studies (Rowghani et al, 2006;Laganá et al, 2011;Abiodun et al, 2014). In the present study, improvement in yolk colors was observed 7 days after feedingthe test diets, and yolk color hanged rapidly in a response to feeding green algae, showing the average values were higher than the control depending on the treatments, then it remained constant until observation of day 42.…”
Section: Egg Qualitysupporting
confidence: 93%
“…In other studies, egg yolk color reached to 13.70 ±1.4 RYC with 20% added duckweed (Indarsih and Tamsil, 2012). In a study where layers were fed with 2% annato seed, pigmentation showed intensively after 28 days, reached to 11.8 (Laganá et al, 2011). The highest yolk color index (5.5) was observed by feeding 1% of costmary (Nobakhtand Moghaddam, 2013).…”
Section: Egg Qualitymentioning
confidence: 84%
See 2 more Smart Citations
“…Rashid et al (2004) used 58 and 67.5% corn in the diet, yolk color score obtained were 8.58±1.70 and 5.9±1.81. Laganá et al (2011) reported feeding 32.24% corn in sorghum and soybean meal based diet without pigment supplementation, yolk color was from 6.5 to 4.0 from day 0 to 28 of observation. As laying birds cannot synthesize egg yolk pigments, egg yolk color strongly depends on the fat-soluble pigments in the diets fed (Gunawardana et al, 2008;Kljak et al, 2012).…”
Section: Egg Quality Assessmentmentioning
confidence: 99%